(untitled) (Bangladesh Journal of Pharmacology, 2017)
The study was conducted to provide the ethnopharmacological bases of the crude extract of seed pods of Ceratonia siliqua in the gastrointestinal spasm, diarrhea and emesis. In segregated rabbit jejunum, it showed dose-dependent (0.01-10 mg/mL) relaxation of spontaneous as well as carbachol (1 µM)-induced contraction. Pre-treatment of segregated rat ileum with C. siliqua, significantly (p<0.0001) suppressed the carbachol (1 µM)-induced contraction similar to atropine (1 µM). These results indicated that C. siliqua possesses spasmolytic activity through possible blockage of muscarinic receptor in jejunum preparations. Furthermore, the crude extract inhibited the castor oil-induced diarrhea, charcoal meal propulsion in mice and copper sulfate-induced retches in chicks in a dose-dependent manner (100, 200, 300 mg/kg). These in vitro and in vivo results indicate that C. siliqua possesses the spasmolytic and antidiarrheal activities mediated possibly through blockage of muscarinic receptors. Thus, this study provides a rationale for its folkloric use. Video Clip of Methodology: 12 min 42 sec Click to watch